Ответы и объяснения

2014-04-06T14:52:56+04:00
3х–у =–10
х²–4ху–у² = –20

у =3х +10
х²–4х(3х +10)–(3х +10)² = –20

             Решаем второе  уравнение:
х²–12х² – 40х – 9х² – 60х – 100 + 20 = 0
–20х² – 100х  – 80 = 0        | : (-20)
х² + 5х + 4 = 0
По теор. Виета  х1 + х2 = - 5,    х1 * х2 = 4          => 
 х1 =  -1          =>      y1 =  3*(-1) +10 = 7
х2 =  -4            =>      y2 =  3*(-4) +10 = -2

Ответ:  (-1 ; 7),    (-4; -2)























Лучший Ответ!
2014-04-06T14:54:34+04:00